Single Molecule Molecular Inversion Probes for High Throughput Germline Screenings in Dystonia - Pogoda, Michaela; Hilke, Franz-Joachim; Lohmann, Ebba; Sturm, Marc; Lenz, Florian; Matthes, Jakob; Muyas, Francesc; Ossowski, Stephan; Hoischen, Alexander; Faust, Ulrike; Sepahi, Ilnaz; Casadei, Nicolas; et al. (Frontiers in Neurology, 2019)
Background: This study’s aim was to investigate a large cohort of dystonia patients for pathogenic and rare variants in the ATM gene, making use of a new, cost-efficient enrichment technology for NGS-based screening. Methods: Single molecule Molecular Inversion Probes (smMIPs) were used for targeted enrichment and sequencing of all protein coding exons and exon-intron boundaries of the ATM gene in 373 dystonia patients and six positive controls with known ATM variants. Additionally, a rare-variant association study was performed. Results: One patient (0.3%) was compound heterozygous and 21 others were carriers of variants of unknown significance (VUS) in the ATM gene. Although mutations in sporadic dystonia patients are not common, exclusion of pathogenic variants is crucial to recognize a potential tumor predisposition syndrome. SmMIPs produced similar results as routinely used NGS-based approaches. Conclusion: Our results underline the importance of implementing ATM in the routine genetic testing of dystonia patients and confirm the reliability of smMIPs and their usability for germline screenings in rare neurodegenerative conditions.